Tools of titans : the tactics, routines, and habits of billionaires, icons, and world-class performers - Ferriss, Timothy (Houghton Mifflin Harcourt, 2016)
"Fitness, money, and wisdom--here are the tools. Over the last two years, #1 New York Times best-selling author Tim Ferriss has collected the routines and tools of world-class performers around the globe. Now, the distilled notebook of tips and tricks that helped him double his income, flexibility, happiness, and more is available as Tools of titans"--Page 4 of cover.